Is All Human Hearing Cochlear? - Seyede Faranak Emami (The Scientific World Journal)
The objective of this cross-sectional study was to investigate the possibility that the saccule may contribute to human hearing. The forty participants included twenty healthy people and twenty other subjects selected from patients who presented with benign paroxysmal positional vertigo to Audiology Department of Hazrat Rasoul Akram hospital (Tehran, Iran). Assessments comprised of audiological evaluations, cervical vestibular evoked myogenic potentials (cVEMPs), recognition of spoken phonemes in white noise (Rsp in wn), and auditory brainstem response to 500 Hz tone burst (ABR500 HZ). Twenty affected ears with decreased vestibular excitability as detected by abnormal cVEMPs revealed decreased scores of Rsp in wn and abnormal findings of ABR500 HZ. Both unaffected and normal ears had normal results. Multiple comparisons of mean values of cVEMPs and ABR500 HZ between three groups were significant (P<0.05, ANOVA). The correlation between RSP in wn and p13 latencies was significant. The peak-to-peak amplitudes showed significant correlation to RSP in wn. The correlation between RSP in wn and the latencies of n23 was significant. In high-level of noisy competing situations, healthy human saccular sensation can mediate the detection of low frequencies and possibly help in cochlear hearing for frequency and intensity discrimination. So, all human hearing is not cochlear.